Сучасний стан та перспективи розвитку машин для протруювання насіння с.-г. культур - Тримбач, С. П.; Вечера, О. М.; Trymbach, S.; Vechera, O. (КНТУ, 2011)
Розглянуто робочий процес нанесення отрутохімікату на насіння. Виявлені недосконалості існуючих протруювачів насіння і запропоновані шляхи їх усунення. The working process of causing of pesticide is considered on seed. Discovered to imperfection of existent treaters and the offered ways of their removal.
Modern state and prospects of development of machines for stainsing of seed of agricultural cultures
Keywords: процес; отрутохімікат; насіння; протруювач